Pemberdayaan Masyarakat Kampung Jepang Manukan dalam Perspektif ACTORS - Senaen, Windriyani Maharani; Casmiwati, Dewi (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2025)
This study analyzes community empowerment practices in Kampung Jepang Manukan, Surabaya, using a descriptive qualitative approach with the ACTORS (Assets, Capacity, Transformation, Organization, Rules, Scale) theory. The results show that the village's main assets, such as thematic ornaments, strategic location, and independently managed culinary MSMEs, have driven a significant transformation from an ordinary settlement into a tourist village with a Japanese cultural nuance. This transformation has social, economic, and aesthetic impacts, but the level of community participation is still limited to around 50% and is mostly dominated by neighborhood association (RT) officials. The organizational structure is centralized with a top-down pattern, while the role of youth and youth organizations is limited to technical implementation. Internal regulations operate informally based on social agreements and supported by community trust, while funding is managed transparently through contributions and donations. The scale of the program's impact is still local, but has the potential to be expanded to the neighborhood association (RW) or sub-district level through institutional strengthening, cross-generational participation, and more intensive promotional strategies.